Sustainable Food Systems The Role of the City - Biel, Robert (UCL Press, 2016)
This book, by a leading expert in urban agriculture, offers a genuine solution to today's global food crisis. By contributing more to feeding themselves, cities can allow breathing space for the rural sector to convert to more organic sustainable approaches. Biel's approach connects with current debates about agroecology and food sovereignty, asks key questions, and proposes lines of future research. He suggests that today's food insecurity - manifested in a regime of wildly fluctuating prices - reflects not just temporary stresses in the existing mode of production, but more profoundly the troubled process of generating a new one. He argues that the solution cannot be implemented at a merely technical or political level: the force of change can only be driven by the kind of social movements which are now daring to challenge the existing unsustainable order. Drawing on both his academic research and teaching, and 15 years' experience as a practising urban farmer, Biel brings a unique interdisciplinary approach to this key global issue, creating a dialogue between the physical and social sciences